HUKUM KONTRAK SEWA MENYEWA (IJARAH) DALAM PENGGUNAAN JASA RAHIM MENURUT PERSFEKTIF ISLAM - Muamar, Muamar; Anjelina, Meriy; Suriyansyah, Ibnu; Maya, Leni; Hasuna, Kamal (Gapenas Publisher, 2023)
Rent or Ijarah is a type of contract that is commonly carried out in everyday life. In the Islamic view, the Ijarah contract is considered a valid contract. Regarding the practice of renting a surrogate mother, of course there are pros and cons that accompany it, and this is the subject of hot debate. Apart from that, this is also a new development in the field of science. Some scholars state that the practice of renting a womb is not in accordance with Islamic moral and ethical principles. However, there are also views that allow it under certain conditions. One of them is the view of Prof. Dr. Journalist Udin from Pakistan. According to him, renting a uterus is only allowed in emergencies and if there is large capacity to care for children if necessary. For example, when this method becomes the only way for a couple to have offspring from their own blood because the wife's uterus is damaged. In the practice of renting a womb, there are procedures that must be adhered to by both the couple renting the womb and the woman who is renting the womb